Evaluasi Screening Dokumen Verifikasi Internal Dalam Menentukan Kodingan Di Era Bpjs - Tri Jenny Minarsih; Herniwanti Herniwanti (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2026)
The implementation of the National Health Insurance (JKN) system through BPJS Kesehatan requires accurate diagnosis and procedure coding to ensure appropriate claim reimbursement. Inaccurate coding and incomplete medical documentation often lead to pending and disputed claims, affecting hospital financial sustainability. This study aimed to evaluate the internal verification document screening process in determining BPJS claim coding at Hospital X and to formulate improvement strategies. A qualitative approach using SWOT analysis was applied to identify internal and external factors influencing the coding and verification process. Data were collected through interviews, document review, and SWOT questionnaires, and analyzed using IFAS and EFAS matrices. The results indicated that internal weaknesses were more dominant, particularly related to coder competency, documentation completeness, and manual screening processes, while external opportunities included regulatory support, coding training availability, and health information technology development. The SWOT analysis placed Hospital X in Quadrant III (Weakness–Opportunity), indicating that leveraging external opportunities to address internal weaknesses is essential to improve coding accuracy and reduce pending and disputed BPJS claims.